Indices of quality surface water bodies in the planning of water resources - Rodríguez-Miranda, Juan Pablo; Serna Mosquera, Jorge Antonio; Sánchez Céspedes, Juan Manuel (Logos Ciencia & Tecnología, 2016)
This paper considers a review of the literature major and significant methods of quality indices of water applied in surface water bodies, used and proposed for assessing the significance of parameters of water quality in the assessment of surface water currents and they are usually used in making decisions for intervention and strategic prevention measures for those responsible for the conservation and preservation of watersheds where these water bodies belong. An exploratory methodology was applied to realize the conceptualization of each water quality index. As a result, it is observed that there are several important methods for determining the water quality index applied in surface water bodies.